2014
DOI: 10.1002/anie.201409744
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Intermolecular Cross Rauhut–Currier Reaction Catalyzed by a Multifunctional Lewis Base Catalyst

Abstract: The highly enantioselective intermolecular cross Rauhut-Currier reaction of different active olefins catalyzed by a multifunctional chiral Lewis base was reported. The RC products were obtained in excellent yields (up to 98 %), high chemo- and enantioselectivity (up to 96 % ee). The reaction could be performed on a gram scale using 1 mol % of the multifunctional phosphine catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 96 publications
0
37
0
1
Order By: Relevance
“…Related to the Rauhut-Currier reaction is the formal (4+1)-cycloaddition of sulfur (S 8 ) with two equivalents of acetylenedicarboxylic esters producing tetraalkyl thiophene-2,3,4,5-tetracarboxylate, a reaction catalyzed by nucleophilic bases such as triethyl phosphite, isoquinoline, pyridine, and N-methylimidazole [378]. An example of catalytic enantioselective intermolecular cross-Rauhut-Currier reaction is given in Scheme 59C [379].…”
Section: The Rauhut-currier Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to the Rauhut-Currier reaction is the formal (4+1)-cycloaddition of sulfur (S 8 ) with two equivalents of acetylenedicarboxylic esters producing tetraalkyl thiophene-2,3,4,5-tetracarboxylate, a reaction catalyzed by nucleophilic bases such as triethyl phosphite, isoquinoline, pyridine, and N-methylimidazole [378]. An example of catalytic enantioselective intermolecular cross-Rauhut-Currier reaction is given in Scheme 59C [379].…”
Section: The Rauhut-currier Reactionmentioning
confidence: 99%
“…An example of catalytic enantioselective intermolecular cross-Rauhut-Currier reaction is given in Scheme 59C [379]. …”
Section: The Morita-baylis-hillman Reactionmentioning
confidence: 99%
“…12 The cross coupling versions of the RC reaction have also been reported. [13][14][15][16][17][18][19][20] Furthermore, the enantioselective RC reactions have been studied and signicant progress has been achieved. [21][22][23][24][25][26][27] Moreover, the RC reaction has been developed for the synthesis of many natural products and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Furthermore, the enantioselective RC reactions have been studied and signicant progress has been achieved. [21][22][23][24][25][26][27] Moreover, the RC reaction has been developed for the synthesis of many natural products and pharmaceuticals. [28][29][30][31][32][33] However, compared to the rich knowledge of experimental studies, much less theoretical studies have been reported on the RC reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Shortly afterwards,p hosphine-catalyzed intramolecular annulation reactions were developed by Tang, Kwon, and other groups. [10] No examples of asymmetric annulation reaction have been developed to build polycyclic compounds by intermolecular sequential annulations to date.T his is because of the existence of some challenges:1 )Complex products are often formed in these reactions;2)sequential chiral centers increase the difficulty in steric-control;a nd 3) multiple diastereoisomers are often obtained in these reactions.A sp art of our interest in asymmetric phosphine catalysis, [11] we aimed to design sequential annulation strategy for construction polycyclic compounds with high diastereoselectivity and enantioselectivity by selecting an appropriate chiral catalyst. [10] No examples of asymmetric annulation reaction have been developed to build polycyclic compounds by intermolecular sequential annulations to date.T his is because of the existence of some challenges:1 )Complex products are often formed in these reactions;2)sequential chiral centers increase the difficulty in steric-control;a nd 3) multiple diastereoisomers are often obtained in these reactions.A sp art of our interest in asymmetric phosphine catalysis, [11] we aimed to design sequential annulation strategy for construction polycyclic compounds with high diastereoselectivity and enantioselectivity by selecting an appropriate chiral catalyst.…”
mentioning
confidence: 99%